Iron-Catalyzed Cross-Electrophile Coupling - Semenya, Julius; Yang, Yuanjie; Picazo, Elias (Synlett, 2024)
Metal-catalyzed cross-coupling reactions have transformed molecular synthesis. Although metal-catalyzed reactions have been used for cross-electrophile coupling reactions, they remain challenging due to homodimer formation. Recently, our group developed an iron-catalyzed cross-electrophile coupling of benzyl halides and disulfides to produce thioethers without the use of an exogenous reductant or photoredox conditions, and with undetectable levels of elimination. This Synpacts article highlights both our design strategy to obviate detrimental homodimer formation and the generality of the method.1 Introduction2 Conceptualization and Development3 Mechanistic Studies and Hypothesis4 Conclusion and Future Directions
Keywords: iron catalysis; cross-electrophile coupling; alkyl halides; disulfides; thioethers